Induced mutations for grain yield in oats. - Arias Fandiño, Jesus (Iowa State University, 2018)
Mutations provide the basie source of genetie variabillty, and thelr nature, rate and frequency of oeeurrenee ha ve a major influenee on the evolutionary pathway of livin~ organisms. The dlscovery of physical and chemlcal mutagens. tof':ether with an understandinp; of thelr modes of aetion on germplasm, has provided a tool to plant scientists for inducing mutations for improving erop eultivars.